2018
DOI: 10.1075/jicb.17019.ted
|View full text |Cite
|
Sign up to set email alerts
|

Teacher perceptions of immersion professional development experiences emphasizing language-focused content instruction

Abstract: The knowledge and pedagogies needed for immersion classrooms are unique and complex. Although there is a growing body of research on immersion pedagogy, there is a dearth of research on professional development (PD) experiences that positively impact immersion teacher practices. This paper focuses on exploring immersion teacher perceptions of PD experiences in the area of language-focused content instruction that have a positive impact on their teaching. The theoretical framework guiding the study is “communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…There are many examples of how teacher education can play an important role in the building and sharing of knowledge between researchers and teachers. This can be found in content-based language instruction with schoolage learners (Lyster, 2019;Lyster et al, 2013;Tedick & Lyster, 2020;Tedick & Zilmer, 2018) as well as in language as subject-matter instruction with adolescents and adults (Erlam, 2008;Sato & Loewen, 2019b). For example, in French immersion, it has been observed that some aspects of students' interlanguage development seem to get stuck on a developmental plateau.…”
Section: Build and Share Knowledgementioning
confidence: 99%
“…There are many examples of how teacher education can play an important role in the building and sharing of knowledge between researchers and teachers. This can be found in content-based language instruction with schoolage learners (Lyster, 2019;Lyster et al, 2013;Tedick & Lyster, 2020;Tedick & Zilmer, 2018) as well as in language as subject-matter instruction with adolescents and adults (Erlam, 2008;Sato & Loewen, 2019b). For example, in French immersion, it has been observed that some aspects of students' interlanguage development seem to get stuck on a developmental plateau.…”
Section: Build and Share Knowledgementioning
confidence: 99%
“…Only a few professional development studies addressed collaborative competence, though none reported explicit instruction on how to collaborate. Teachers in Tedick and Zilmer (2018) collaborated on multiple assignments throughout the workshop. Similar collaboration was facilitated by Cammarata and Haley (2018), leading to teachers realizing how collaboration could be incorporated into their districts and schools.…”
Section: Collaborative Competencementioning
confidence: 99%
“…Banegas (2020), Cammarata and Tedick (2012), and Tedick and Zilmer (2018) all reported teachers reflecting and developing a sense of professional empowerment and agency. However, besides these generalizations of professional development as reflection, little reference was found in specific ways of reflecting, particularly outside professional development participation.…”
Section: Reflective Competencementioning
confidence: 99%
“…In ISLA, a good deal of the pedagogy-based research also comes from teacher professional development initiatives that have emerged in response to research findings. This includes investigations of how experienced teachers explore ways of focusing on language within content-based language teaching via professional development courses (Tedick & Zilmer, 2018); studies investigating teachers collaborating with researchers to develop and implement instructional materials focusing learners' attention on language in subject-matter French immersion classes (Lyster, Collins, & Ballinger, 2009;Lyster, 2019); and investigations of the role of the teacher in creating opportunities for learners to co-construct knowledge of academic language in content and language integrated learning (CLIL) classrooms (Nikula, 2015;Van Gorp & Van den Branden, 2015).…”
Section: Theory Research and Pedagogymentioning
confidence: 99%